The effect of socio-economic inequalities and dietary diversity on the food insecurity levels of urban households: a case study of Niğde province, Turkey - Gürer, Betül (Progress in Nutrition, 2021)
This study provided a deep insight to what extent the socio-economic, demographic and nutritional characteristics of the households were related to different degrees of food insecurity by using the generalized ordered logit model. The cross-sectional data was collected from 391 urban households in Niğde province of Turkey by conducting face-to-face interviews. According to the study results, the households that were found to be more likely to exposure the food insecurity include households with unemployed and less educated household heads, households with low monthly income and low food expenditure per capita and households with a large size and with children. The study also provided new insights about nutritional adequacy of households in the context of food security. It was found that individuals who consumed protein-containing foods ever day had a 90% less risk of becoming food insecure than those who never or only sometimes consumed these foods. Similarly, it was found that individuals who sometimes consumed iron-containing foods had a 67% less risk of being food insecure than those who never consumed these foods. Policies for poverty reduction, enhancing employment opportunities, reducing of the cost of nutrient-rich foods along food supply chain and diversification of nutritious foods production could contribute to improve the food security status of households.